Effect of CaO-FeO-MnO system solid solution on the hydration activity of tri-component f-CaO in steel slag. (20th November 2019) - Ji, Xinyi; Hou, Jiwei; Liu, Yanchao; Liu, Jiaxiang
Highlight: The calcium iron manganese phase was classified as f-CaO in four type steel slags. The distribution of finite solid solution in tri-component f-CaO is uniform. Partial solid solution is still unhydrated after hydrated under autoclaved for 3 h. Tri-component f-CaO causes the poor hydration activity of steel slag. Abstract: The ingredients and formation mechanism of calcium iron manganese phase were confirmed and analyzed to comprehend further the hydration activity of tri-component f-CaO in four type steel slags. BSE-EDS analysis indicates that the tri-component f-CaO in four type steel slags was a phase of CaO·aFeOx ·bMnOy system and the mean values of nFe /nCa, nMn /nCa and (nFe + nMn )/nCa were focused on nearby 0.12, 0.08 and 0.2, respectively. According to the relevant element ratio, the simply simulated experiments of tri-component f-CaO were conducted that the CaO-FeO-MnO system finite solid solution and a new crystalline phase of Ca2 Fe2 O5 were formed. The formation mechanism of CaO-FeO-MnO system finite solid solution was described briefly. By means of SEM-EDS, the microstructure of synthetic tri-component f-CaO was observed, and the analyses of XRD/TG-DTA and thermodynamic theory were applied to the hydration activity. The results show that the hydration percentage of tri-component f-CaO was about 80% after autoclaved for 3 h, and more than two times that of after hydrated at ambient temperature for 36 h. The CaO-FeO-MnO system solid solution was one of the critical factors which causes the poor hydration activity of tri-component f-CaO. This theoretical investigation will lay a foundation for building materials and solid waste fields.